The cavity under the Amery Ice Shelf, East Antarctica - Benjamin Galton-Fenzi; Maraldi, C; Richard Coleman; John Hunter (2008)
Ocean circulation under ice shelves and associated rates ofmelting and freezing are strongly influenced by the shape of the sub-ice-shelf cavity. We have refined an existing method and used additional in situ measurements to estimate the cavity shape under the Amery Ice Shelf, East Antarctica. A finite-element hydrodynamic ocean-tide model was used to simulate the major tidal constituents for a range of different sub-Amery Ice Shelf cavity water-column thicknesses. The data are adjusted in the largely unsurveyed southern region of the ice-shelf cavity by comparing the complex error between simulated tides and in situ tides, derived from GPS observations. We show a significant improvement in the simulated tides, with a combined complex error of 1.8 cm, in comparison with past studies which show a complex error of ¡5.3 cm. Our bathymetry incorporates ice-draft data at the grounding line and seismic surveys, which have provided a considerable amount of new data. This technique has particular application when the water column beneath ice shelves is inaccessible and in situ GPS data are available.